Routledge handbook of food in Asia
1 online resource
Keywords: Throwing new light on how colonisation and globalization have affected the food practices of different communities in Asia, the Routledge Handbook of Food in Asia explores the changes and variations in the region's dishes, meals and ways of eating. By demonstrating the different methodologies and theoretical approaches employed by scholars, the contributions discuss everyday food practices in Asian cultures and provide a fascinating coverage of less common phenomenon, such as the practice of wood eating and the evolution of pufferfish eating in Japan. In doing so, the handbook not only covers a wide geographical area, including Japan, Indonesia, Vietnam, Singapore, India, China, South Korea and Malaysia, but also examines the Asian diasporic communities in Canada, the United States and Australia through five key themes: Food, Identity and Diasporic Communities Food Rites and Rituals Food and the Media Food and Health Food and State Matters. Interdisciplinary in nature, this handbook is a useful reference guide for students and scholars of anthropology, sociology and world history, in addition to food history, cultural studies and Asian studies in general.